Study on the Overburden Failure Law of High-Intensity Mining in Gully Areas With Exposed Bedrock - Yi, Tan; Han, Xu; Weitao, Yan; Wenbing, Guo; Erhu, Bai; Tingye, Qi; Dawei, Yin; Bingyuan, Hao; Hao, Cheng; Minghao, Shao (Frontiers in Earth Science, 2022)
Most hilly areas are dotted with gullies, some of which contain plenty of water, especially in rainy seasons. Once surface water penetrates the underground working face, it will lead to an increased water inflow of the working face. Even worse, it may induce water and sand burst accidents. To prevent geological disasters such as water and sand burst and ensure the safe production in coal mines, it is necessary to reveal the development law of “two zones” in the overburden caused by shallow-seam fully mechanized top coal caving high-intensity mining in hilly areas with exposed bedrock, and timely grasp the communication between the water flowing fractured zone (WFFZ) and the water in surface gullies. In this study, the P2 working face of the exposed bedrock surface in DN Coal Mine is taken as the research object. First, the characteristics of overburden movement and the law of exposed bedrock surface movement in areas with exposed bedrock were investigated through similar simulation. Meanwhile, the temporal-spatial evolution of overburden movement caused by shallow-seam fully mechanized top coal caving high-intensity mining was clarified, and the mode of overburden movement was revealed. Moreover, the reason why the water inflow of the underground working face increases suddenly was theoretically explained. The following conclusions were drawn. Under shallow-seam fully mechanized top coal caving high-intensity mining, the WFFZ of the P2 working face is directly connected to the exposed bedrock surface, and the movement of the overburden is subject to the typical “two-zone” mode. The development height of the WFFZ is greater than the value in the traditional “three-zone” mode calculated according to the empirical formulas. The ratio of the WFFZ height to the mining thickness is 43.75. Under the “two-zone” mode, a water flowing channel exists in the overburden near the open-off cut and the stopping line. When the surface water source is in the right position, the water inflow of the underground working face will increase suddenly.